Upland rice yield enhanced by early nitrogen fertilization on previous palisade grass - Momesso, Letusa [UNESP]; Crusciol, Carlos A. C. [UNESP]; Soratto, Rogério P. [UNESP]; Tanaka, Katiuça S. [UNESP]; Costa, Claudio H. M.; Cantarella, Heitor; Kuramae, Eiko E. (My University, 2020)
High grain yields of upland rice (Oryza sativa L.) can be achieved in no-tillage systems. However, managing nitrogen (N) fertilization for rice in succession to forage grasses is a challenge because forage residues change N cycling and increase microbial immobilization of N, thereby reducing N availability to the subsequent cash crop. In the present study, two field experiments were conducted to determine if applying all or part of the N fertilizer on preceding palisade grass (Urochloa brizantha) and ruzigrass (Urochloa ruziziensis) or their desiccated residues immediately before rice seeding can supply N to the subsequent rice crop. Forage biomass yield (8–16 Mg ha− 1), N accumulation, and N supply to the subsequent upland rice were highest when all of the N fertilizer was applied on forage grasses at 50, 40 or 35 days before rice seeding (DBS), as opposed to the conventional split application at rice seeding and at tillering. On average, the grain yield of upland rice was 54% higher in succession to palisade grass compared with ruzigrass. The grain yield of rice was higher when N was applied to palisade grass at 35 DBS and ruzigrass at 50 DBS, reaching 5.0 Mg ha− 1 and 3.7 Mg ha− 1, respectively. However, applying N to ruzigrass was less effective for increasing upland rice yields since the yields did not differ from the treatments with the conventional split application. Adjusting the time of N application to forage grasses to increase the grain yields of subsequent upland rice is a sustainable alternative that can promote the economic viability of upland rice production.
Keywords: Brachiaria spp; Cover crop; Nitrogen supply; Oryza sativa; Sustainable agriculture